Effect of microstructure on cleavage fracture of thick-section quenched and tempered S690 High-Strength steel: - Bertolo, V.M.; Jiang, Q.; Walters, C.L.; Pupovich, V.A. (2020)
One of the main challenges in applying thick-section high-strength steels (HSS) at arctic condition in offshore and maritime industry is to maintain a sufficient level of toughness to prevent brittle failure. An aspect that requires special attention is the through-thickness microstructural variation which may result in different local mechanical responses affecting the overall material’s fracture behaviour. This paper presents an experimental study combining microstructural investigation and sub-sized fracture toughness testing at −100 °C of different sections of 80 mm S690QL steel aimed to evaluate the effect of microstructure on cleavage fracture. In addition, different crack depth to width ratios (a/W) were used to investigate the constraint effect, while different notch orientations were applied to assess the effect of rolling orientation. Results show lower fracture toughness for themiddle of the plate, which was attributed to the presence of large Nb-rich inclusions which may feature pre-existing cracks and/or defects in the inclusion/matrix interface and also often distributed as clusters. It was also observed that a/W ratio plays an important role in fracture toughness showing shallow-notched specimens with substantially higher fracture toughness than deep cracked specimens.Moreover, microstructural features such as inclusions aligned parallel to the pre-crack can ease the crack propagation and contribute to a reduction in fracture toughness.